TXNDC5 contributes to rheumatoid arthritis by down‐regulating IGFBP1 expression. (21st December 2017) - Li, J.; Xu, B.; Wu, C.; Yan, X.; Zhang, L.; Chang, X
Summary: The thioredoxin domain‐containing 5 (TXNDC5) gene is associated with susceptibility to rheumatoid arthritis (RA) and exhibits increased expression in the synovial tissues. TXNDC5 is also associated strongly with diabetes, a metabolic disease characterized by interrupted insulin signalling. This study investigated whether TXNDC5 contributes to RA via the insulin signalling pathway. In this study, RA synovial fibroblast‐like cells (RASFs) transfected with an anti‐TXNDC5 small interfering RNA (siRNA) were analysed with an insulin signaling pathway RT 2 profiler polymerase chain reaction (PCR) array and an insulin resistance RT 2 profiler PCR array. The PCR arrays detected significantly increased expression of insulin‐like growth factor binding protein 1 (IGFBP1) in RASFs with suppressed TXNDC5 expression. The result was verified using real‐time PCR and Western blot analyses. Significantly elevated IGFBP1 expression and decreased interleukin (IL)‐6 secretion were also detected in culture medium of transfected RASFs. Furthermore, decreased IGFBP1 mRNA and protein expression levels were detected in RA synovial tissues. Additionally, significantly increased apoptosis and decreased cell proliferation and cell migration were observed in RASFs transfected with the anti‐TXNDC5 siRNA, whereas transfection with the anti‐IGFBP1 siRNA or a mixture of the anti‐IGFBP1 and anti‐TXNDC5 siRNAs restored normal cell proliferation, migration and IL‐6 level in RASFs. Insulin‐like growth factor (IGF) has potent prosurvival and anti‐apoptotic functions, and IGFBP1 can suppress IGF activity. Based on the results of the present study, we suggest that TXNDC5 contributes to abnormal RASF proliferation, migration and IL‐6 production by inhibiting IGFBP1 expression. Abstract : Inhibiting TXNDC5 expression up‐regulates insulin‐like growth factor binding protein 1 (IGFBP1) level and down‐regulates IL‐6 secretion in RA synovial fibroblast‐like cells (RASFs). IGFBP1 has significantly decreased expression in rheumatic arthritis synovial tissues compared with samples of osteoarthritis. TXNDC5 expression stimulates RASF proliferation, migration and IL‐6 production by inhibiting IGFBP1 expression.